Pelatihan penguatan ekonomi pesantren melalui pemberdayaan usaha santri di Pondok Pesantren Darul Fikri Kabupaten Kubu Raya - Supriaman; Agustiar, Memet; Luthfi, Faishol; Taufik, M. Iman; Arminingsih, Diah (Penamas: Journal of Community Service, 2025)
Islamic boarding schools play a strategic role in producing a generation that is not only outstanding in religious aspects but also economically independent. However, many Islamic boarding schools still face limitations in optimally managing their economic potential. Therefore, this activity aims to enhance students' capabilities in entrepreneurship and business management. This initiative is designed as a training programme focused on creative and digital economy-based entrepreneurship, business management, and the optimisation of pesantren resources. The methods employed include theoretical training, hands-on practice, and ongoing mentoring to enable students to develop and manage businesses independently. This training creates a sustainable business ecosystem within the boarding school, enhances students' entrepreneurial skills, and increases the number of productive business units that can serve as income sources for the boarding school. Through this training, positive impacts are generated, including the enhancement of students' entrepreneurial knowledge and the management of Darul Fikri Islamic Boarding School, enabling the school to become a model of an economically independent boarding school and to contribute positively to the surrounding community.